Effects of pasture type on tissue composition and sensorial meat quality of lambs raised under the organic livestock system - Hamdi H.; Znaïdi I.A.; Kraïem K.; Majdoub-Mathlouthi L. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
In organic livestock system, animals should have access to pasture. This study aims to determine the effects of the pasture type (PT) used to fattened lambs according to organic conditions. Fifty four Barbarine lambs with an initial average weight of 24.06±5.01 kg and 8 month-old were divided into two homogeneous groups. Each group received 200 g of organic oat hay and 400 g of organic farmer concentrate (63.7% barley, 18.2% broad bean, 13.6% faba bean, 4.5% mineral vitamin supplement) with access either to natural pasture (NP) or a cultivated green barley pasture (BP) both organic certified. Six lambs from each group were slaughtered at an average weight of 35 kg. Results obtained indicated that NP lambs had higher lean proportions in leg (+3.13%) and lumbar region (+5.88%) than those reread on BP, but no effects of PT were found for fat proportions (P>0.05). As for instrumental meat color parameters, redness (a*) were higher on NP lambs Longissimus lumborum (LL) and Semitendinosus (ST) muscles. Yellowness (b*) was not affected by PT for both muscles (P>0.05). The meat sensory quality was slightly affected by PT. ST muscle of NP lambs was more tender (7.15 vs 5.51; P<0.001) than those produced on BP. Feeding lambs on NP tended to increase meat juiciness and flavor (P < 0.10). However, fat degree was higher in LL muscle of BP lambs (P<0.05). Green barley pasture can be used as an alternative feed resource to fed lambs according to organic system especially in the drought season.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)